Evaluation of polyherbal formulation for antihypertensive activity in albino rats - Pratibha; Gaurav Sharma; Sudipta Kumar Rath (Wolters Kluwer Medknow Publications, 2021)
Background: Hypertension (HTN) is a multifactorial clinical condition and therefore can be managed in multiple pathways. Long time period use of modern antihypertensive drugs is associated with a spectrum of toxic and side effects. Modern antihypertensive drugs are not ideally effective owing to dependence, side effects, and cost. However, therapeutic interventions using herbal drugs for HTN have gained widespread attention worldwide. Aim: The aim of the study is to evaluate the antihypertensive activity of polyherbal formulation (NIA/DG/2015/01) as an adjuvant with modern antihypertensive drug or as a stand-alone drug in cadmium chloride (CdCl2)-induced hypertensive albino rat model. Methods: The polyherbal formulation (NIA/DG/2015/01) comprises the bark of Terminalia arjuna (Roxb.) W and A, the root of Withania somnifera (Linn.), the rhizome of Nardostachys jatamansi DC., the root of Boerhaavia diffusa (Linn.), and whole plant of Convolvulus pluricaulis Choisy. All the herbs were separately extracted in aqueous medium. Polyherbal formulation (90 mg/kg., p.o.), was evaluated using the CdCl2-induced hypertensive rat model using the Verapamil as a standard reference drug. HTN was induced in albino rats by intraperitoneal administration of CdCl2 (0.1% CdCl2 solution) 1 mg/kg/day for 15 days. After 15 days, intervention was started for 28 days, and blood pressure (B.P.) was measured in every 7th day. Results: Polyherbal formulation significantly reduced (P < 0.001, one-way analysis of variance followed by Tukey's multiple comparison test and Dunnett's multiple comparison test) systolic and diastolic B.P. in CdCl2-induced HTN model when compared with Verapamil. Conclusion: Polyherbal formulation (NIA/DG/2015/01) possesses significant antihypertensive activity.